2022
DOI: 10.3390/ijerph19063265
|View full text |Cite
|
Sign up to set email alerts
|

Political Populism, Institutional Distrust and Vaccination Uptake: A Mediation Analysis

Abstract: Politics is ubiquitous in public health, but vaccines had never been weaponized to instill distrust to gain political advantage. In pandemic and post-pandemic scenarios, populist political parties could use vaccine-related issues to generate distrust in evidence-based knowledge. Therefore, some questions arise. What impact could populist political parties impinge on vaccination uptake rates through sowing political discontent? What could the medical institutions do to avoid the adverse effects that these polit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 73 publications
2
7
0
Order By: Relevance
“…The analysis of correlations in our study showed that populist attitudes are positively correlated with conspiracy beliefs about COVID-19, age (older participants are more populist), right-wing political orientation, and negatively correlated with trust in government institutions, perception of the spread of the virus, concern about COVID-19, acceptance of anti-COVID-19 vaccines, and compliance with anti-COVID-19 measures. These results are consistent with those found in the literature (e.g., Ehrke et al, 2023;Recio-Román et al, 2022).…”
Section: Discussionsupporting
confidence: 94%
“…The analysis of correlations in our study showed that populist attitudes are positively correlated with conspiracy beliefs about COVID-19, age (older participants are more populist), right-wing political orientation, and negatively correlated with trust in government institutions, perception of the spread of the virus, concern about COVID-19, acceptance of anti-COVID-19 vaccines, and compliance with anti-COVID-19 measures. These results are consistent with those found in the literature (e.g., Ehrke et al, 2023;Recio-Román et al, 2022).…”
Section: Discussionsupporting
confidence: 94%
“…In 2020, vaccine acceptance in European countries was influenced by mistrust in the safety and efficacy of vaccines [7], perceived risk of communicable disease, and socio-demographic determinants or specific population groups [1,[5][6][7][8][12][13][14][15][16]. Further barriers to vaccine acceptance were ideological reasons, lack of institutional confidence and confidence among healthcare workers (HCWs) [17][18][19][20][21], public perceptions of specific vaccines, inconvenience of vaccination services, and religious reasons or groups [7,21]. In Finland, official websites were widely used to increase vaccination coverage, informing citizens about vaccines and their safety.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the public dissemination of clinical trial results that refutes the benefits of Hydroxychloroquine, such as the RECOVERY trial in the United Kingdom, diminished public enthusiasm toward Hydroxychloroquine (Lasco & Yu, 2021; Lee et al, 2021; Saag, 2020). As a populist arsenal, studies show that pharmaceutical messianism can also be countered through information dissemination and social marketing strategies, including in online platforms (Lee et al, 2021; Recio-Román et al, 2022; Saag, 2020). Hence, there is a need to ensure that online public information regarding this “panacea” and other treatment options is highly searchable and easily understandable.…”
Section: Discussionmentioning
confidence: 99%
“…The “invocation of knowledge claims,” which may be detrimental to public health, was among the populist arsenals used by politicians during the COVID-19 pandemic ( Lasco, 2020 ; Sabahelzain et al, 2021 ). As populists arsenals, these claims can lead to difficulty achieving herd immunity coverage, new outbreaks, and a vicious distrust of social institutions ( Recio-Román et al, 2022 ). Thus, these arsenals could present as obstacles to the effective and efficient delivery of public health services and adversely affect population health in the process.…”
Section: Introductionmentioning
confidence: 99%